2019
DOI: 10.1016/j.heliyon.2019.e02256
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of water absorption and chloride ion penetration of rice straw ash and microsilica admixed pavement quality concrete

Abstract: The effects of rice straw ash (RSA) and microsilica (MS) on durability properties (water absorption and chloride ion penetration) of M40 grade Pavement Quality Concrete (PQC) were studied. Ten concrete samples were prepared by partially substituting cement with RSA and MS in various proportions. A significant reduction was observed in the water absorption and chloride ion penetration in concrete samples with an increase in the curing age as well as with an increase in the proportion of MS and RSA. The maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…There are different ways available in literature to test the capacity of concrete to absorb water like saturated water absorption test, water sorptivity test, etc. [60] [61]. The procedure to determine the coefficient of permeability ('k') provided in IS 3085 [37] was followed in this study, and its values for all concrete samples are shown in Figure 14.…”
Section: Water Permeabilitymentioning
confidence: 99%
“…There are different ways available in literature to test the capacity of concrete to absorb water like saturated water absorption test, water sorptivity test, etc. [60] [61]. The procedure to determine the coefficient of permeability ('k') provided in IS 3085 [37] was followed in this study, and its values for all concrete samples are shown in Figure 14.…”
Section: Water Permeabilitymentioning
confidence: 99%
“…As shown in Tables 5-7, based on granulations of three types of Shootar materials, the most suitable mixing design that agrees well with the specifications was selected. The design had the following ingredients: (1) crushed gravel (12-25) mm, 30% by weight; (2) broken gravel (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) mm, 30% by weight; (3) natural washed sand (0-8), 40 mm by weight; (4) the mixing plan is done according to the specifications shown in Table 5; (5) consumable cement is considered type-II from Tehran-Iran cement factory having a 400 kg per cubic meter grade; (6) the water-cement ratio 38% obtained with an average slump of 65 mm from Mahshahr-Iran water. It must be pointed out that the mixing scheme was drawn up on the basis of specifications seen in Table 5.…”
Section: Mixing Ratiosmentioning
confidence: 99%
“…Bagheri et al [6] conducted a number of experiments and observed that concrete electrical resistance could increase five times by replacing 12% microsilica with cement. Pandey and Kumar [7] performed an evaluation on the water absorption, and chloride ion penetration of rice straw ash and microsilica admixed pavement quality concrete. They derived two equations for both the initial and secondary rate of water absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Automatically, concrete-containing large silica particles are more resistant to corrosion attack. On the contrary, in concrete made with the addition of a water-entraining agent [18], chloride ions enter into concrete more easily, especially in young concrete [19,20]. Corrosion attack on the concrete reinforcement surface causes cracks on the surface of concrete and a decrease in bonding force of reinforcement.…”
mentioning
confidence: 99%